Respostas

2014-08-19T09:36:28-03:00
Olá, Alinnecosta1!

Usaremos o teorema de Pitágoras (h² = c² + c²). 

A)
Hipotenusa: 10
Cateto 1: x
Cateto 2: x

h² = c² + c²
10² = x² + x²
100 = 2x²
2x² = 100
x² = 100 / 2
x² = 50
x = √50
x = √2.5²
x = 5√2

B)
Hipotenusa: x
Cateto 1: 12
Cateto 2: 5

h² = c² + c²
x² = 12² + 5²
x² = 144 + 25
x² = 169
x = √169
x = 13

C)
Hipotenusa: 8
Cateto 1: x
Cateto 2: 4

h² = c² + c²
8² = x² + 4²
64 = x² + 16
x² + 16 = 64
x² = 64 - 16
x² = 48
x = √48
x = √2².2².3
x = 4√3

3 4 3